Spring-summer temperatures since AD 1780 reconstructed from stable oxygen isotope ratios in white spruce tree-rings from the Mackenzie Delta, northwestern Canada - Porter, Trevor J.; Pisaric, Michael F.J.; Field, Robert D.; Kokelj, Steven V.; Edwards, Thomas W.D.; deMontigny, Peter; Healy, Richard; LeGrande, Allegra N. (Climate Dynamics, 2013)
This is the accepted manuscript of an article published by Springer Verlag. High-latitude δ18O archives deriving from meteoric water (e.g., tree-rings and ice-cores) can provide valuable information on past temperature variability, but stationarity of temperature signals in these archives depends on the stability of moisture source/trajectory and precipitation seasonality, both of which can be affected by atmospheric circulation changes. A tree-ring δ18O record (AD 1780-2003) from the Mackenzie Delta is evaluated as a temperature proxy based on linear regression diagnostics. The primary source of moisture for this region is the North Pacific and, thus, North Pacific atmospheric circulation variability could potentially affect the tree-ring δ18O-temperature signal. Over the instrumental period (AD 1892-2003), tree-ring δ18O explained 29% of interannual variability in April-July minimum temperatures, and the explained variability increases substantially at lower-frequencies. A split-period calibration/verification analysis found the δ18O-temperature relation was time-stable, which supported a temperature reconstruction back to AD 1780. The stability of the δ18O-temperature signal indirectly implies the study region is insensitive to North Pacific circulation effects, since North Pacific circulation was not constant over the calibration period. Simulations from the NASA-GISS ModelE isotope-enabled general circulation model confirm that meteoric δ18O and precipitation seasonality in the study region are likely insensitive to North Pacific circulation effects, highlighting the paleoclimatic value of tree-ring and possibly other δ18O records from this region. Our δ18O-based temperature reconstruction is the first of its kind in northwestern North America, and one of few worldwide, and provides a long-term context for evaluating recent climate warming in the Mackenzie Delta region. Financial support for this project is gratefully acknowledged: Aboriginal Affairs and Northern Development Canada grant; NSERC Discovery grant and Northern Supplement (M. Pisaric); Northern Scientific Training Program (T. Porter); NSERC Postgraduate Scholarship (T. Porter). Resources supporting this work were provided by the NASA High-End Computing (HEC) Program through the NASA Center for Climate Simulation (NCCS) at Goddard Space Flight Center.